Implementation of active learning strategies: The case of secondary schools: Learning strategies - Dagnew, Asrat (Revija za elementarno izobraževanje, 2023)
The purpose of this study was to investigate implementation of active learning strategies at secondary schools in Ethiopia. To conduct the study, descriptive survey design was employed. A total of 109 teachers were participated in the study through systematic sampling technique. The study was complemented by mixed method approach that employed both qualitative and quantitative data collection tools such as observation checklists, questionnaires and interviews. The quantitative data was analyzed using frequency, percentage, mean value, grand mean and mean ranking and the qualitative data was analyzed in organizing, summarizing and interpreting narrative description. The findings of the study reported that most of the respondents have perceived active learning strategies positively. In spite of their good perceptions, their practices of active learning strategies were low. The major factors affecting the effective implementation of active learning strategies were large class size, student lack of interest, shortage of time, teachers lack of commitment, students’ beliefs and perceptions and diversity of student interest were among the most influential factors hindering its implementation. Finally, it is recommended that responsible bodies should reorganize the conditions and facilitate necessary inputs for the implementation of active learning strategies.